Catalog of the recent taxa of the families Epitoniidae and Nystiellidae (Mollusca: Gastropoda) with a bibliography of the descriptive and systematic literature - Brown, Leonard G.; Neville, Bruce D. (Zootaxa, 2015)
This catalog includes 1,487 names recent genera, subgenera, species, subspecies, varieties, and forms that have been referred to the families Epitoniidae and Nystiellidae as well as a bibliography of the descriptive and systematic literature associated with these names. For the names covered herein, we make a determination of whether the name is an available name, as that term is defined in the International Code of Zoological Nomenclature (“ICZN”) and, based on a review of the literature listed in the bibliography, indicate whether the taxon is a potentially valid name or a probable synonym. This catalog includes not only includes a list of names, but also includes information on type material, type localities and species’ geographic, bathymetric and size ranges. We also suggest generic assignments for many of the species level taxa listed in this work. We herein designate Scalaria acuta J. Sowerby, 1812, to be the type species of Clathrus Agassiz, 1837, designate Scalaria raricostata G.B. Sowerby II, 1844b, to be the type species of Variciscala de Boury, 1909a, designate Turbiniscala sexcosta Jousseaume, 1912, to be the type species of Turbiniscala de Boury, 1909a, and designate Scala dubia ‘G. B. Sowerby II’ de Boury, 1912b to be the type species of Foliaceiscala de Boury, 1912b.